الأمن و السلامة في المنشآت النفطية و فاعلية تطبيق المعايير و الأنظمة الدولية (OSHA, GHS)‎: د. سالم مبارك صالح بن قديم ، د. ليبيا عبود صالح باحويرث - جامعة الأندلس للعلوم و التقنية د. سالم مبارك صالح بن قديم ، د. ليبيا عبود صالح باحويرث (مجلة الأندلس للعلوم التطبيقية, 2023)
The safety and security of oil fields installations arised from the significance of oil as strategic raw material which having its danger. In order to guarantee its security and safety as well as continuity of operations of the these installations, specific technical departments and boards had been founded for the purpose of establishing scientific standards and measures to identify safety in the installations and to avoid dangers. The study has presented the applied techniques used for protecting oil installations from dangers, international boards and departments for safety and occupational health, and applied standards as well as the extent of their effectiveness in the oil installations. Conclusions of the study point out to growing interest to improvising skills of human resources to be adapted with developments and controlling them, and regular follow up to confirm the efficiency of applying safety actions according to the known international standards.